Skeletal muscle capillary function: contemporary observations and novel hypotheses - Poole, David C.; Copp, Steven W.; Ferguson, Scott K.; Musch, Timothy I. (My University, 2014)
The capillary bed constitutes a vast surface that facilitates exchange of O2, substrates and metabolites between blood and organs. In contracting skeletal muscle, capillary blood flow and O2 diffusing capacity, as well as O2 flux, may increase two orders of magnitude above resting values. Chronic diseases, such as heart failure and diabetes, and also sepsis impair these processes, leading to compromised energetic, metabolic and, ultimately, contractile function. Among researchers seeking to understand blood–myocyte exchange in health and the basis for dysfunction in disease, there is a fundamental disconnect between microcirculation specialists and many physiologists and physiologist clinicians. While the former observe capillaries and capillary function directly (muscle intravital microscopy), the latter generally use indirect methodologies (e.g. post-mortem tissue analysis, 1-methyl xanthine, contrast-enhanced ultrasound, permeability–surface area product) and interpret their findings based upon August Krogh's observations made nearly a century ago. ‘Kroghian’ theory holds that only a small fraction of capillaries support red blood cell (RBC) flux in resting muscle, leaving the vast majority to be ‘recruited’ (i.e. to initiate RBC flux) during contractions, which would constitute the basis for increasing surface area for capillary exchange and reducing capillary–mitochondrial diffusion distances. Experimental techniques each have their strengths and weaknesses, and often the correct or complete answer to a problem emerges from integration across multiple technologies. Today, Krogh's entrenched ‘capillary recruitment’ hypothesis is challenged by direct observations of capillaries in contracting muscle, which is something that he and his colleagues could not do. Moreover, in the peer-reviewed scientific literature, application of a range of contemporary physiological technologies, including intravital microscopy of contracting muscle, magnetic resonance, near-infrared spectroscopy and phosphorescence quenching, combined with elegant in situ and in vivo models, suggest that the role of the capillary bed, at least in contracting muscle, is subserved without the necessity for de novo capillary recruitment of previously non-flowing capillaries. When viewed within the context of the capillary recruitment hypothesis, this evidence casts serious doubt on the interpretation of those data that are based upon Kroghian theory and indirect methodologies. Thus, today a wealth of evidence calls for a radical revision of blood–muscle exchange theory to one in which most capillaries support RBC flux at rest and, during contractions, capillary surface area is ‘recruited’ along the length of previously flowing capillaries. This occurs, in part, by elevating capillary haematocrit and extending the length of the capillary available for blood–myocyte exchange (i.e. longitudinal recruitment). Our understanding of blood–myocyte O2 and substrate/metabolite exchange in health and the mechanistic basis for dysfunction in disease demands no less.
Keywords: Capillary bed; Skeletal muscle; Capillary blood flow; Capillary recruitment; Blood‐muscle exchange theory